EMERGENCE OF NON-ALBICANS CANDIDA AND USE OF CHROMAGAR FOR SPECIATION OF CANDIDA IN A RESOURCE-LIMITED SETTING - SHEFALI GARG; ANURADHA MALHOTRA; LOVEENA OBEROI; SAPNA BATRA; KAMALDEEP SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Candida infections, especially those caused by non-albicans Candida species, have become increasingly common in recent years. These species’ early isolation and identification are essential for their effective management. This study aimed to evaluate the efficacy of CHROMagar for the speciation of Candida. Methods: All clinical samples received in the microbiology laboratory from April 2023 to March 2024 were processed as per microbiological criteria. The isolates that revealed Gram-positive budding yeast cells on Gram staining were further identified and speciated using CHROM agar and conventional methods. Results: A total of 749 Candida were isolated from various clinical samples. Candida albicans was the most common species isolated (46.41%), followed by Candida glabrata (23.63%), Candida krusei (14.15%), Candida parapsilosis (9.2%), and Candida tropicalis (6.5%) while sensitivity and specificity of CHROM agar were 100% for C. glabrata and C. krusei and 98.3% and 100% for C. albicans while 100% sensitivity and 94.2%, 96% specificity for C. parapsilosis and C. tropicalis, respectively, when compared to conventional methods. Conclusion: CHROM agar’s performance was nearly identical to that of conventional methods. Compared to time-consuming, technically complex, and costly conventional methods, using this medium is quick, easy to use, and economical.